"You Don't Feel": The Experience of Youth Benzodiazepine Misuse in Ireland. Issue 2 (15th March 2018) - Murphy, Kevin D.; Lambert, Sharon; McCarthy, Suzanne; Sahm, Laura J.; Byrne, Stephen
ABSTRACT: There are negative effects to inappropriate use of benzodiazepines, yet the percentage of young people in Ireland experimenting with benzodiazepines has increased. There is a paucity of research about why Irish young people misuse benzodiazepines. In this study, people between 18 and 25 years attending substance misuse services in the south of Ireland ( N = 13) were interviewed in a semi-structured style between June 2012 and April 2013. Content analysis was performed. The main motivations for benzodiazepine misuse were to self-regulate negative emotions and to induce dissociation from their environment. Interviewees also described the consequences of benzodiazepine misuse, such as disengagement from family relationships and other protective environments such as school and sports clubs. The consequences of chronic misuse were discussed, such as the compulsion to take more benzodiazepines despite experiencing severe side-effects. The incidence of paradoxical aggression on benzodiazepines is also explored. Education about benzodiazepines and their risks to young people, families, and the public may reduce benzodiazepine misuse. Future research on the role of trauma and mental health in young people's substance misuse is needed.